Observed protein structures - Feigenson, Gerald W. (Henry Stewart Talks, 2020)
Protein secondary structures: α helix, β-sheet, turns, and collagen, Collagen properties, The ‘protein fold’, Protein arrangement according to type of fold, superfamily and family
Reviewed at 2022/11/27